Blok źreniczny u dziecka z pierwotnie przetrwałym hiperplastycznym ciałem szklistym – opis przypadku - Kanigowska, Krystyna; Grałek, Mirosława; Grajkowska, Wiesława; Pronicki, Maciej (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The purpose of this paper is to present the case of a patient with PHPV, in whom the complication in a form of pupillary block glaucoma was observed as a result of idiopathic and complete lens dislocation into the anterior chamber. Material and methods: Examination was performed on 3 months old boy with grey pupilla reflex, noted from the birth, in the right eye. Microphthalmia, subcapsular cataract and anterior-posterior form of PHPV was found in that eye. The patient was qualified to surgical treatment. Before the appointed time of operation the increased intraocular pressure and significant globe enlargement were noted. The reason of that was pupillary block caused by lens dislocation into the anterior chamber. One-step surgical procedure: trabeculectomy, lensectomy and cutting out the retrolenticular fibrous membrane, was performed in urgent course. Results: Performed complicated and difficult surgical treatment resulted in normalizing IOP and created good conditions for vision rehabilitation for the child. Postoperatively the detachment of the choroid was noted as a transient complication. Conclusions: In this case luxated lens and pupillary block was caused by constriction of retrolenticular fibrous membrane. Early surgical intervention is necessary to prevent progressive pathologic changes in eyes with this developmental disorder and to obtain the best possible visual results.